Barth Syndrome: From Mitochondrial Dysfunctions Associated with Aberrant Production of Reactive Oxygen Species to Pluripotent Stem Cell Studies - Saric, Ana; Andreau, Karine; Armand, Anne-Sophie; Møller, Ian M.; Petit, Patrice X. (Frontiers in Genetics, 2016)
Mutations in the gene encoding the enzyme tafazzin, TAZ, cause Barth syndrome (BTHS). Individuals with this X-linked multisystem disorder present cardiomyopathy (often dilated), skeletal muscle weakness, neutropenia, growth retardation and 3-methylglutaconic aciduria. Biopsies of the heart, liver and skeletal muscle of patients have revealed mitochondrial malformations and dysfunctions. It is the purpose of this review to summarize recent results of studies on various animal or cell models of Barth syndrome, which have characterized biochemically the strong cellular defects associated with TAZ mutations. Tafazzin is a mitochondrial phospholipid-lysophospholipid transacylase that shuttles acyl groups between phospholipids and regulates the remodeling of cardiolipin (CL), a unique inner mitochondrial membrane phospholipid dimer consisting of two phosphatidyl residues linked by a glycerol bridge. After their biosynthesis, the acyl chains of CLs may be modified in remodeling processes involving up to three different enzymes. Their characteristic acyl chain composition depends on the function of tafazzin, although the enzyme itself surprisingly lacks acyl specificity. CLs are crucial for correct mitochondrial structure and function. In addition to their function in the basic mitochondrial function of ATP production, CLs play essential roles in cardiac function, apoptosis, autophagy, cell cycle regulation and Fe-S cluster biosynthesis. Recent developments in tafazzin research have provided strong insights into the link between mitochondrial dysfunction and the production of reactive oxygen species (ROS). An important tool has been the generation of BTHS-specific induced pluripotent stem cells (iPSCs) from BTHS patients. In a complementary approach, disease-specific mutations have been introduced into wild-type iPSC lines enabling direct comparison with isogenic controls. iPSC-derived cardiomyocytes were then characterized using biochemical and classical bioenergetic approaches. The cells are tested in a ‘‘heart-on-chip’’ assay to model the pathophysiology in vitro, to characterize the underlying mechanism of BTHS deriving from TAZ mutations, mitochondrial deficiencies and ROS production and leading to tissue defects, and to evaluate potential therapies with the use of mitochondrially targeted antioxidants.